Has knowledge improved economic growth? Evidence from Nigeria and South Africa - Olatunji Abdul Shobande; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
This study examines whether knowledge causes economic growth in Africa's two leading economies: Nigeria and South Africa. Using the Vector Autoregressive and Vector Error Correction approach, the findings show cointegration among the variables. The speed of convergence of the variables to their long-term mean values is relatively higher for South Africa than for Nigeria. In the short run, it is observed that knowledge unidirectionally Granger causes growth for Nigeria, whereas bidirectional causality is observed for South Africa. The higher correlation between knowledge and growth in South Africa reflects the success of greater investment in education. Nigeria must increase investment in education and modern infrastructure to converge to South Africa's growth trajectory. Moreover, for Nigeria, (i) knowledge unidirectionally Granger cause growth, (ii) evidence of bidirectional causality flow is apparent between trade, the economic incentive and growth and (iii) health unidirectionally Granger cause knowledge. As for South Africa: (i) there is bidirectional causality between knowledge, trade openness and growth, whereas investment and economic incentive, unidirectionally Granger causes growth, (ii) investment, trade openness and health unidirectionally Granger cause knowledge and (iii) economic incentive unidirectionally Granger cause trade openness. In conclusion, this paper argues that a transformed education system can provide the knowledge base essential for promoting and sustaining economic growth.
Keywords: 330; Convergence; Growth performance; Knowledge-based economy; Nigeria; South Africa